Pengaruh Jenis dan Lama Penyangraian pada Mutu Kopi Robusta (Coffea robusta) - Bukhori Thomas Edvan; Rachmad Edison; Made Same (Jurnal Agro Industri Perkebunan, 2016)
The process of roasting the coffee beans will produce a good quality of taste and aroma. To conduct this research activity in the roasting researchers used a minimalist roaster machine (mini roaster). This study was conducted to determine the effect of temperature and duration of roasting, and the interaction of temperature and long roasting on the quality of Robusta coffee.The experiment was conducted in analysis laboratory, plant laboratory, and THP State Polytechnic of Lampung in November 2014 to February 2015. The experiments were performed with a patterned factorial randomized block design with 2 factors and each treatment combination was repeated 3 times. The first factor is the temperature which consists of three levels i.e. 190 oC, 200 oC, and 210 oC. The second factor is roasting duration wich consist of three levels i.e. 10 minutes, 16 minutes and 22 minutes. The results showed that the temperature 190 oC was the best in the roasting. Roasting duration 10 minutes was the best in the roasting process. Temperatures above 190 oC and duration above 10 minutes will reduce the quality of the coffee. The combination of the best treatment in the process of roasting seen from the middle value in the variable water content, juice coffee and caffeine levels are long roasting temperature of 190 oC and 10 minutes. Based on advanced testing methods Tukey confidence level of 95%, no interaction by the temperature and duration of roasting the coffee extract and the water content, but shows the interaction of the ash content and the caffeine content.Keywords: quality of Robusta coffee, roasting duration, roasting temperaturePermalink:Â http://jurnal.polinela.ac.id/index.php/AIP/article/view/34